Caracterização e valorização de resíduos de gabinetes de microcomputadores de mesa - Kohl, Claudia Adriana (Universidade do Vale do Rio dos Sinos, 2014)
This study aimed to characterize and enhance waste desktop computer, without screen. There were five distinct steps: the mass balance of the desktop computer, without screen, and their componetes effect; calculate recycling rates of the desktop computer, and their components; make the characterization of the chemical elements of the material that makes up the desktop computer, and; classified as a hazardous waste according to ABNT NBR 10004:2004 Solid Waste - Classification. Been achieved-through the steps: the manual disassembly of the case; separating and weighing the components as well as the constituent materials; the calculation of recycling rates; chemical analyzes by fluorescence spectrometry X-rays, and; comparison of the chemical elements found in analyzes of the Annexes to ABNT NBR 10004: 2004. The results showed that the desktop computer, without screen study, have an average weight of 10.56 kg and 81.71% mass consists of the motherboard, the power supply and the cabinet enclosures (lid and body other parts). The other components are the floppy drives, CD drives, IDE cables, hard disk and coolers represent 18.29% of the mean weight of the cabinets. The recycling rate achieved for the desktop computer, without screen, was 96.66% this rate represents the amount of material likely to be recycled in the samples studied. Chemical analyzes performed, we found a total of 47 chemical elements of the Periodic Table, of these, we mention nickel and antimony (considered carcinogens), chlorine and bromine (halogen elements considered) as well as barium, lead and chromium (considered elements that confer dangerous waste). Soon, classified themselves the desktop computer this study, as Class I (hazardou) waste, according the method used in this work.
Characterization and enhance of waste desktop computer, without screen
Keywords: REEE; Resíduo de microcomputadores; Reciclagem de computadores; Desktops; WEEE; Computers waste; Computer recycling; ACCNPQ::Engenharias::Engenharia Civil